2004
DOI: 10.1073/pnas.0406837101
|View full text |Cite
|
Sign up to set email alerts
|

Survival factor-induced extracellular signal-regulated kinase phosphorylates BIM, inhibiting its association with BAX and proapoptotic activity

Abstract: The “BH3-only” proapoptotic BCL-2 family members initiate the intrinsic apoptotic pathway. A small interfering RNA knockdown of BIM confirms this BH3-only member is important for the cytokine-mediated homeostasis of hematopoietic cells. We show here that the phosphorylation status of BIM controls its proapoptotic activity. IL-3, a hematopoietic survival factor, induces extracellular signal-regulated kinase/mitogen-activated protein kinase-mediated phosphorylation of BIM on three serine sites (S55, S65, and S10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
243
1
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(266 citation statements)
references
References 30 publications
(41 reference statements)
17
243
1
3
Order By: Relevance
“…Stimulation of FL5.12 pro-B cells with IL-3 promotes the ERK1/2-dependent phosphorylation of Bim EL . 32 In common with other studies, 27 this has no effect on the interaction of Bim EL with Bcl-2 or Mcl-1, but rather prevented Bim EL from interacting with Bax; 32 this would presumably have the effect of preventing the oligomerization of Bax and cell death. Mutation of three phosphorylation sites in Bim EL (Ser59Ala, Ser69Ala and Ser104Ala) abolished phosphorylation in vivo, enhanced Bim EL -Bax interactions and enhanced cell death following withdrawal of IL-3.…”
Section: Erk1/2-dependent Phosphorylation Antagonizes Bim Elmentioning
confidence: 58%
See 3 more Smart Citations
“…Stimulation of FL5.12 pro-B cells with IL-3 promotes the ERK1/2-dependent phosphorylation of Bim EL . 32 In common with other studies, 27 this has no effect on the interaction of Bim EL with Bcl-2 or Mcl-1, but rather prevented Bim EL from interacting with Bax; 32 this would presumably have the effect of preventing the oligomerization of Bax and cell death. Mutation of three phosphorylation sites in Bim EL (Ser59Ala, Ser69Ala and Ser104Ala) abolished phosphorylation in vivo, enhanced Bim EL -Bax interactions and enhanced cell death following withdrawal of IL-3.…”
Section: Erk1/2-dependent Phosphorylation Antagonizes Bim Elmentioning
confidence: 58%
“…There is some precedent for this in the ability of c-Jun to provide a docking site for JNK, which then phosphorylates the c-Jun dimer partner, JunD, which otherwise fails to bind JNK directly. 40 Despite these reports, 26,32 other studies suggest that Bim L is not phosphorylated following activation of ERK1/2. [29][30][31]33 Aside from caveats regarding different cell types or stimulation conditions, an alternative explanation for this confusion is that another Bim splice variant is actually being studied.…”
Section: Phosphorylation Of Other Bim Isoforms By Erk1/2: a Question mentioning
confidence: 96%
See 2 more Smart Citations
“…47 In addition, it has been suggested that phosphorylation of Bim by ERK1/2 inhibits its interaction with Bax. 48 Whether ERKs phosphorylate Bim EL at serine 65 in sympathetic neurons maintained in the presence of NGF is unknown.…”
Section: Post-translational Regulation Of Bim and Bad By Phosphorylationmentioning
confidence: 99%